THE RELATION BETWEEN CLIMATE VARIATION AND THE INCIDENCE OF DIARRHEA IN SEMARANG 2011-2015 (CASE STUDY IN WORKING AREA OF PUSKESMAS BANDARHARJO SEMARANG) - Anna Nur Nahari; Budiyono Budiyono; Suhartono Suhartono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Working area of Puskesmas Bandarharjo is one of the area that has the cases of diarrhea which is quite high. The prevalence of diarrhea is 17 per 1000 population. Had been known that the climate in Semarang on 2002-2011, there is some elements that has been changed include the increase of air temperature average- the average was 0.10C every year and the humidity increase up to 1.6% every year. These condition was marked by the shortening of the rainy season and the dry season was getting longer. Working area of Puskesmas Bandarharjo lies in the coast which has high air temperature. Climate change will affect to the development of microorganism that cause some diseases, one of them is diarrhea. The purpose of this study was determine the relation between climatic variation with the cases of diarrhea in working area of Puskesmas Bandarharjo Semarang. This study was cross sectional study. The analysis was using rank spearman.The descriptive result showed that the average of diarrhea since 2011-2015 is 167 cases; rainfall is 180.27 mm/month; air temperature is 28.400C; humidity is 76.13%. Statistical analysis show that there is positive correlation between rainfall variability with the incidence of diarrhea ( p = 0.0001 ; r = 0.664 ) , there is a negative correlation between variations in air temperature with the incidence of diarrhea ( p = 0.018 ; r = - 0.304 ) , there is a correlation among the positive variation of the humidity with the incidence of diarrhea ( p = 0.0001 ; r = 0.554 ) . From the results of this study concluded that there is a correlation between climatic variations in the incidence of diarrhea in Puskesmas Bandarharjo Semarang.